Analysis of Indonesian Intelligence as Transnational Crime of Football Gambling - Celine Tjandra (Eduvest - Journal of Universal Studies, 2024)
Football gambling is a global phenomenon that not only impacts economic, but also social and legal aspects. As a sport that is very popular in the world, it does not rule out the possibility of the involvement of various parties from various countries in this crime, thus becoming a serious problem in the form of transnational crime. Gambling is an act that has been considered criminal according to various laws and regulations that apply in many countries in the world. In Indonesia, although gambling is prohibited, this practice remains widespread, especially through online platforms that are difficult to control by law enforcement officials. In Indonesia, gambling is considered an illegal act and is regulated in the Criminal Code (KUHP). Article 303 of the Criminal Code prohibits all forms of gambling and provides criminal sanctions for gambling offenders. This research aims to analyze Indonesia's vulnerability to the transnational crime of football gambling. This research uses a qualitative method by conducting in-depth analysis based on data and news found based on the theory of vulnerability in Indonesia. The results show that there are several main factors that increase Indonesia's vulnerability to transnational football gambling.